PENGARUH PERBEDAAN SUHU TERHADAP PENETASAN TELUR IKAN GURAMI ( Osphronemus gouramy Lac) - Muhammad Sugihartono; Masdinar Dalimunthe (Universitas Batanghari Jambi, 2010)
This study aims to determine the success of hatchery fish, gurami (O. gouramy Lac), which maintained controlled by the temperature difference, so that can know the optimal temperature for hatching eggs. This research was conducted at Fish Seed (BBI) Sungai Alai, Muara Tebo Jambi.Egg samples used in this study were egg gourami (O. gouramy Lac) obtained from the mass spawning of carp Batanghari parent as much as 1440 eggs by stocking the 120 eggs / container. The container used in the study is an aquarium measuring 60 x 40 x 30 cm 12 units, which filled with water of 20 liter / container and each is equipped with aerator and the water heater thermostat.The design used was Completely Randomized Design (CRD) with 4 (four) maintenance medium temperature treatment of 260C, 280C, 300C and 320C, each with 3 (three) replicates. Observations are made to the success of hatchery fish gourami (O. gouramy Lac) and water quality parameters: temperature, pH and turbidity. A good temperature for hatching eggs are 300C and 320C in which the degree of hatching eggs amounted to 98.05% and 94.72%. Water quality parameters during the study support of fish life.Keyword : The temperature difference, Fish Eggs Hatching